Dermatological evaluation in dogs with atopic dermatitis treated with full-spectrum high cannabidiol oil: a pre study part 1 - Mariga, Carollina; Souza Silva Mateus, Ana Lúcia; dos Santos Dullius, Ângela Isabel; da Silva, Ana Paula; Martins Flores, Mariana; Vasconcelos Soares, André; Amazonas, Erik; Tadeu Lemos Pinto Filho, Saulo (Frontiers in Veterinary Science, 2023)
Dermatological consultations represent a great part of the small animal medical clinic routine. And canine atopic dermatitis (CAD) is a common skin disease that affects a significant amount of dogs, making it a relevant consideration in clinical practice . The role of the endocannabinoid system on skin homeostasis has been described and its deregulation contributes to dermatopathies. Its function in specialized skin cells reveals an expressive therapeutic potential. Due to the difficulties and the growing scientific evidence of the therapeutic benefits of cannabis on animals, this work aimed to evaluate the anti-inflammatory effects of cannabis-derived oil in the treatment of CAD. Fourteen canines diagnosed with CAD were divided into two groups: T: full spectrum high cannabidiol (CBD) cannabis oil, 2,5 mg/kg; and C: control group (treated with olive oil alone). The effectiveness was evaluated based on the degree of pruritus, dermatological evaluation (CADESI-4) and histopathological evaluation of the skin including mast cell count. Despite the theoretical basis, there were no significant results obtained between the compared treatments. Thus, it can be concluded that although full spectrum high cannabinoids therapy presents a promising approach to immunological diseases, further research is required in order to establish the actual effective cannabinoid ratio within the myriad possible combinations and for multi-target therapy of CAD.